United Republic of Tanzania : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
This paper on the United Republic of Tanzania's Poverty Reduction Strategy reports that increases in investments in infrastructure such as roads, telecommunications, mining, and tourism have been recorded owing to increased inflows of foreign direct investments and domestic revenue effort. Significant improvement in performance is evident in areas such as primary education and road network. The current levels of delivery of services require further improvements in quantity and quality, which call for sustained investments in all sectors.